Peran Influencer Gaming Dalam Meningkatkan Customer Engagement dan Purchase Intention pada Pemain Mobile Legends - Alya Chantika; Usep Suhud; Meta Bara Berutu (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the effects of influencer attributes, attractiveness, expertise, trustworthiness, and credibility on customer engagement and purchase intention among Mobile Legends players. A quantitative approach with an explanatory research design was employed. Data were collected through an online questionnaire distributed to 252 Mobile Legends players who met the research criteria. The measurement instrument used Likert scale, and data were analyzed using Structural Equation Modeling (SEM) with the assistance of IBM SPSS and AMOS. The findings indicate that influencer attributes have a positive and significant impact on both customer engagement and purchase intention. However, customer engagement shows a positive but insignificant effect on purchase intention. These results suggest that high levels of engagement do not necessarily translate directly into purchase intention in the context of online gaming.